Pengaruh Etos Kerja Dan Lingkungan Kerja Terhadap Produktivitas Kerja Pegawai Pada Kantor Kementerian Agama Kabupaten Bima - Widia Aryani; Ikbal Irawan; Mawar Hidayanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the influence of work ethic and work environment on employee productivity at the Office of the Ministry of Religious Affairs, Bima Regency. Work ethic and work environment are two crucial factors that can affect individual performance within an organization, especially in public institutions that demand professional and efficient public services. The research method used is quantitative with an associative approach. Data were collected through questionnaires distributed to 60 respondents who are active employees at the Ministry of Religious Affairs Office in Bima Regency. The data analysis techniques used include validity and reliability tests, multiple linear regression, t-test, and F-test to determine the partial and simultaneous influence of the independent variables (work ethic and work environment) on the dependent variable (work productivity). The results showed that work ethic has a positive and significant influence on employee productivity. The work environment also has a positive and significant impact on productivity. Simultaneously, work ethic and work environment significantly influence employee productivity. These findings indicate that improving work ethic and enhancing the work environment should be key considerations for management in their efforts to boost overall employee performance. Therefore, efforts to increase productivity can be achieved by fostering a positive work culture and providing a supportive work environment.